2014
DOI: 10.1136/archdischild-2013-304803
|View full text |Cite
|
Sign up to set email alerts
|

The potential for neonatal organ donation in a children's hospital

Abstract: With around 60 paediatric organ donors in the UK annually, there does appear significant potential for donation within the neonatal population. Reconsideration of current infant brain stem death guidelines is required to allow parents the opportunity of donation after neurological determination of death, together with mandatory training in organ donation for neonatal teams, which will also facilitate donation after circulatory definition of death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
39
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 20 publications
2
39
0
1
Order By: Relevance
“…pDCDD Donor Potential Studies (n = 12) PICU or neonatal ICU (NICU) pDCDD potential included five retrospective NICU studies (44,45,81,84,85); five retrospective (42,43,47,48,82) and one prospective PICU studies (86). Two articles (15,26) were commentaries on studies that estimated potential pDCDD ( Table 3).…”
Section: Impact Of Pdcddmentioning
confidence: 99%
“…pDCDD Donor Potential Studies (n = 12) PICU or neonatal ICU (NICU) pDCDD potential included five retrospective NICU studies (44,45,81,84,85); five retrospective (42,43,47,48,82) and one prospective PICU studies (86). Two articles (15,26) were commentaries on studies that estimated potential pDCDD ( Table 3).…”
Section: Impact Of Pdcddmentioning
confidence: 99%
“…None of these were referred for donation (personal communication). Charles et al 4 have reported the significant potential for donation within the neonatal population in an audit of pediatric death within a tertiary unit, where in a period of just over 6 years, 34 of 84 infant deaths could have been potential donors. Eleven of these could have been potential donors after "brain stem" death.…”
Section: Discussionmentioning
confidence: 98%
“…Currently, neonatal organ donation does not occur in the United Kingdom, largely due to the fact that death verification/certification standards prohibit use of neurological criteria for diagnosing "brainstem death" in infants between 37 weeks' gestation and 2 months of age. 4 This is not the case in other European countries, Australasia, and the United States.…”
mentioning
confidence: 88%
“…Over recent years, this disparity has been highlighted by others7 8 and, as such, the guidance relating to brain death determination in infants is currently under scrutiny by both the Royal College of Paediatrics and Child Health and the UK Donation Ethics Committee. This is important as a recent study suggested that up to 13% of babies dying in a UK specialist neonatal unit between 37 weeks’ gestation and 2 months, theoretically, could fulfil BSD criteria and become donors, if it were not for current restrictions 9. Hopefully, expected changes in guidance will allow this potential expansion of the donor pool to be realised in the near future.…”
mentioning
confidence: 99%
“…Recent studies have explored the potential for DCD organ donation in neonatal intensive care units. Charles et al 9 recently reported the potential for neonatal organ donation from a single tertiary/quaternary UK neonatal unit. Over a 6-year period, they identified 34 potential DCD donors, representing 40% of all deaths over the time period.…”
mentioning
confidence: 99%